Analysis of the relationship between objective and subjective indicators of quality of life in terms of access to urban services in the context of old zone of Urmia - amin mahmodi azar; Rahim hashempour; sid momen fovad marashi (تحقیقات کاربردی علوم جغرافیایی)
In recent decates, the subject of quality of living in city and the satisfaction of citizens from their environments has attarced the views the most of researchers and international institutes around the world. Because of its importance, UN to publish a report annually in which different cities around the world ranked and compared through the quality of life. Quality of living talk about different indices and one of its important indices is access to the city services which in turns would decrease some of the city problems such as slums and irregular construction, land speculation and etc. This research tries to analysis the city quality of living according to the standards of services access in cities. So, quality of service access was analysed in objective and subjective sections in old zone of Urmia. The research method is descriptive-analytic and we use questioner, different models such as AHP and network analysis and fuzzy techniques, Pierson coefficient for our study. Results show that satisfaction of city-service access has a very meaningful statistic impact on the subjective factors of quality of living and as it increases more, we have more subjective quality. These results tell planners that key factors would have great impacts and roles on the satisfaction of the life of citizens.